Relational spirituality in psychotherapy : healing suffering and promoting growth - Sandage, Steven J.; Rupert, David (David Alan); Stavros, George; Devor, Nancy G. (American Psychological Association, 2020)
"Spiritual and existential struggles tell a story about the quality of clients' lives, beyond what clinicians can learn from their mental health symptoms alone. This book presents the Relational Spirituality Model (RSM) of psychotherapy, a creative clinical process that engages existential themes to help people make sense of profound suffering or trauma. To promote healing and growth, practitioners using the RSM provide a secure and challenging therapeutic space, while guiding clients as they explore ways of relating to the sacred in their lives. In this model, therapeutic change is seen as an intense yet safe process of movement and tension between dwelling and seeking, stability and disruption. Assessment and intervention strategies focus on developmental systems-attachment, differentiation, and intersubjectivity-to restructure relationships with the self, others, and the sacred. In depth clinical case examples demonstrate how to respect diverse client perspectives on suffering and trauma, and apply the RSM in individual, couple, family, and group psychotherapy. Readers will find new ways of working within the spiritual, existential, religious, and theological concerns that infuse their clients' struggles and triumphs"--